Modèles équilibre pour l’analyse duale - Kempeneers, Martin; Beckers, Pierre; Almeida, José Paulo Moitinho de; Pereira, Orlando J. B. Almeida (European Journal of Computational Mechanics, 2003)
The pure dual analysis is one of the first methods developed to perform the estimation of the global discretization error of finite elements analysis. It is based on the comparison of two finite elements solutions, one of which being of the displacement type (kinematically admissible), the second one being of the equilibrium type (statically admissible). This work presents two methods allowing to create equilibrium elements. The first one which can be seen as an hybrid method, allows to compute high-order equilibrium solutions of 2D problems. The second method is of the pure equilibrium type. Its recent extension to 3D problems with tetrahedral mesh is presented here. Those approaches enabled us to present some results of global error estimation by dual analysis.